2017
DOI: 10.1002/app.45580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lignin extraction methods on microstructure and mechanical properties of lignin‐based carbon fibers

Abstract: In order to optimize the use of residues of enzymatic hydrolysis of corn stalk (REHCS) and explore the low‐cost and sustainable raw material substitute for carbon fibers, three types of lignin samples were extracted from REHCS by various extraction methods, and then they were converted into carbon fibers (CFs) by electrospinning, thermostabilization, and carbonization under the same process conditions. The microstructure and mechanical properties of the three types of carbonized fibers were different. The CFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 27 publications
(36 reference statements)
3
23
0
Order By: Relevance
“…Based on these results, the types of lignin influenced the microstructure of lignin-based carbon materials. In the literature, Shi et al reported the impact of three types of lignin by various extraction methods on the microstructure and mechanical properties of lignin-based carbon fibers [32]. Obviously, these results were similar with the previous results.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Based on these results, the types of lignin influenced the microstructure of lignin-based carbon materials. In the literature, Shi et al reported the impact of three types of lignin by various extraction methods on the microstructure and mechanical properties of lignin-based carbon fibers [32]. Obviously, these results were similar with the previous results.…”
Section: Resultssupporting
confidence: 87%
“…There was also report about the impact of three types of lignin by various extraction methods on microstructure and mechanical properties of lignin-based carbon fibers [30]. In general, many parameters such as the types of lignin, treatment methods, carbonization temperature, carbonization time, activated solution, etc, had an effect on the structure and property of lignin-based carbon materials [13,31,32]. In this paper, the experimental results further indicated the influences of the synthetic methods on the lignin-based carbon materials.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the PPL exhibited relatively higher molecular weights compared to DPL, which suggests that the higher molecular weight lignin fractions were more easily obtained through the PAW process compared to the DAW process. Hence, the PPL with higher molecular weights that were obtained in this study would be suitable as a raw material in the synthesis of lignin-based carbon fibers [33].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon fibers are lightweight and high-strength materials that are useful to produce reinforced composites to be employed in industrial sectors related to transport, like automotive and aerospace applications. Although initially lignin-based carbon fibers did not achieve the mechanical properties of traditional carbon fibers, more recent advances in spinning techniques have improved their performance [465]. Electrospinning and melt-spinning are more advantageous fiber processing techniques, but the structure of the lignin, determined by the biomass nature and isolation process, has great influence over the fiber processing [466][467][468].…”
Section: Lignin-derived Carbon Materialsmentioning
confidence: 99%